The Interface between Cultural Intelligence and Interlanguage Pragmatics: The Case of Gratitude Speech Act - Zia Tajeddin; Mohammad Momenian (Iranian Journal of Applied Language Studies, 2012)
The process of globalization entails the acquisition of a construct, cultural intelligence, with which EFL students can function appropriately in intercultural situations. This study was, first, intended to find the relationship between cultural intelligence and the use of expressions of gratitude by Iranian EFL learners. Second, it sought to determine whether there were any significant differences between low and high culturally intelligent EFL learners in the way they used expressions of gratitude in English. To this end, 118 intermediate learners were selected through convenient sampling, with their proficiency level being controlled. A discourse completion test (DCT) for the expressions of gratitude and a cultural intelligence scale were given to the participants of the study. Learners’ DCT responses were rated on a five-point Likert scale and then analyzed. Statistical tests including Pearson Correlation Coefficient and t-test were used to investigate the research questions. The results of the analysis revealed that there was not a significant relationship, either positive or negative, between cultural intelligence and use of expressions of gratitude. Furthermore, no difference was found between the two groups, high and low culturally intelligent, in the way they used English expressions of gratitude. These findings have implications for the instruction of pragmatic competence.